2020
DOI: 10.3390/molecules25225271
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamides Target Leishmania amazonensis Arginase Selectively

Abstract: Caffeic acid and related natural compounds were previously described as Leishmania amazonensis arginase (L-ARG) inhibitors, and against the whole parasite in vitro. In this study, we tested cinnamides that were previously synthesized to target human arginase. The compound caffeic acid phenethyl amide (CAPA), a weak inhibitor of human arginase (IC50 = 60.3 ± 7.8 μM) was found to have 9-fold more potency against L-ARG (IC50 = 6.9 ± 0.7 μM). The other compounds that did not inhibit human arginase were characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…In particular, the interaction with Asp141 was also found in complexes of LaARG with quercetin, quercitrin and isoquercitrin, where the two hydroxyls in catechol group of the flavonoids formed a hydrogen bond with Asp141 [18]. Moreover, in a study of cinnamide inhibitors evaluated in LaARG, it was observed that some of these inhibitors share Van der Waals interactions with the same residues as compound 1 and 2 (His139, Val149, and His154), as well as electrostatic interactions with Asp245 and Glu288 [20]. Furthermore, several of these Van der Waals interactions were also found with chalcone inhibitors in L. infantum [22].…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In particular, the interaction with Asp141 was also found in complexes of LaARG with quercetin, quercitrin and isoquercitrin, where the two hydroxyls in catechol group of the flavonoids formed a hydrogen bond with Asp141 [18]. Moreover, in a study of cinnamide inhibitors evaluated in LaARG, it was observed that some of these inhibitors share Van der Waals interactions with the same residues as compound 1 and 2 (His139, Val149, and His154), as well as electrostatic interactions with Asp245 and Glu288 [20]. Furthermore, several of these Van der Waals interactions were also found with chalcone inhibitors in L. infantum [22].…”
Section: Discussionmentioning
confidence: 86%
“…On the other hand, biological activity and cytotoxicity studies indicated that both LmARG inhibitors had leishmanicidal activity being compound 1 as active as the reference drug Glucantime (32 and 35 µM, respectively) and more selective against the amastigote stage of the parasite than the three reference drugs used for the treatment of leishmaniasis (Table 3). In the same context, several cinnamides derivatives were reported as LaARG inhibitors and tested against L. amazonensis promastigotes, but only caffeic acid phenylamide (CAPA) showed biological activity with an IC 50 of 82.56 µM, however, no data over its effect against mammalian cell lines are available [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of phenolic acid derivatives (e.g., cinnamic acid) and the related natural dihydroxycinnamic compounds (e.g., catechol-containing caffeic, chlorogenic, or rosmarinic acids) revealed the antileishmanial and/or antiplasmodial potency [ 15 , 16 ]. Hence, rosmarinic acid analogues and new caffeic acid-derivative amides were synthesized and tested to target human and L. amazonesis arginases, respectively [ 17 , 18 ]. In an attempt to determine the potential arginase-inhibitor binding modes, the computer-aided structure-based protocol was applied indicating that cinnamoyl or 3,4-hydroxycinnamoyl motifs are crucial for the mechanism of arginase inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…The following supporting information can be downloaded at: , Sections S1–S7; Figures S1–S72; Tables S1–S8. References [ 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ] are cited in the Supplementary Materials.…”
mentioning
confidence: 99%